ADAKAH PENGARUH PERNYATAAN PRESIDEN GUS DUR TERHADAP PERILAKU KURS RP/US$, 1 JANUARI 1999 â 30 APRIL 2002?: STUDI EMPIRIS DENGAN METODE BOX JENKINS (ARIMA) - Kuncoro, Mudrajad; Inayah, Hikmah (Journal of Indonesian Economy and Business, 2003)
This study attempts to analysis Rupiah/US$ exchange rate using ARIMA (Autoregressive Integrated Moving Average) method. It explores to what extent impacts of political variable, in term of the (former) President Abdurrachman Wachidâs (Gusdur) statement, on the exchange rate fluctuation. Two main sources of data were used: first, daily exchange rates of Rp/US$ over the period of Januari 1st, 1999 to April 30th , 2002; second, media reports on Gus Durâs statement which comed up every Friday. The empirical results found that yesterdayâs exchange rates and trend influenced the current exchange rates significantly, as shown by AR (1) and trend variable. More importantly, depreciation of Rupiah was caused by political (news) variable, especially Gus Durâs statement. The last indicates the evidence of Friday effect in the case of Rp/US$ during Gus Dur regime.Keywords: ARIMA Method; Autoregressive; Moving Average; News (Gus Durâs statement); Trend